Evaluation of compost of swine waste as amendment for production of cut wallflowers (Matthiolaincana) - Riera, Nicolas Iván (2018)
The intensification of swine production systems generates accumulation of manure, which if not stabilized can generate negative impact on the environment. At the same time, the demand for organic materials to amend the soil for the production of cut flowers has increased. The objective of the work was to evaluate the use of swine compost as an amendment in different proportions through the growth of wallflowers (Matthiolaincana). The trial consisted of four treatments with three repetitions each: T1: 15l/m2 , T2: 30l/m2 , T3: 60 l/m2 and T4: no incorporation of compost. A 12m x 1m flowerbed was used, divided into 12 experimental units. Phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K), nitrates (NO3 - ), pH and electrical conductivity (EC) in a ratio of 1 / 5 (v/v sample / water), and organic matter (OM) were analyzed for each treatment. In addition compost quality and the presence of Escherichia coli and Salmonella spp. were also analyzed. The carbon / nitrogen (C / N) ratio of the compost was 14.1 and the respirometric index (IRE) of 0.55 mg O2 g -1 MO h-1 According to the TMECC (2001)[1], these values establish that the compost was stable and mature, on the other hand, the absence of pathogens E. coli and Salmonella ssp. was verified. The high electrical conductivity (CE) (5.53 dS.m-1 ) and the high concentration of sodium (11464 mg/l) in the compost were limiting for the development of wallflower (wallflower plant). The amendment with doses superior to 30 l/m 2 , caused a reduction of the growth and consequently lower quality of the floral stick. The evaluated swine compost is viable as an amendment to produce cut wallflowers up to 15l/m2.